The challenge of Islam: secularism and its dangers to Muslims' beliefs and practices - Abdul Rahim, Adibah (2009)
Secularism is the most serious challenge of modernity posed by the West. Its main ideology is to liberate man from the religious and metaphysical values and expel religion from the practical aspect of man’s life. It clearly presents its materialistic viewpoint which is cut off from Divine, Transcendent or Supernatural principles and does not refer to and is isolated from Revelation. In terms of its intensity and scope as well as its discernable effects upon people’s mind, the repercussion of secularism is so pervasive and universal. It gives a great impact on every facet of life including individual and family lives as well as educational, political, economic and social-cultural realm. Most importantly, secularism affects the very tenets of traditional religious beliefs and practices. This paper tries to focus on the danger of secularism and its principles which are contradict to the religious worldview.